2016
DOI: 10.1161/cir.0000000000000405
|View full text |Cite|
|
Sign up to set email alerts
|

Duration of Dual Antiplatelet Therapy: A Systematic Review for the 2016 ACC/AHA Guideline Focused Update on Duration of Dual Antiplatelet Therapy in Patients With Coronary Artery Disease: A Report of the American College of Cardiology/American Heart Association Task Force on Clinical Practice Guidelines

Abstract: *These members of the Evidence Review Committee are listed alphabetically, and all participated equally in the process. Members reported no relationships with industry and other entities relevant to this report. Background:The optimal duration of dual antiplatelet therapy (DAPT) after implantation of newer-generation drug-eluting stents (DES) remains uncertain. Similarly, questions remain about the role of DAPT in long-term therapy of stable post-myocardial infarction (MI) patients. aim:Our objective was to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(66 citation statements)
references
References 70 publications
(188 reference statements)
1
63
0
Order By: Relevance
“…reviewed in ), and it is the acute thrombotic event that precipitates a myocardial infarction, stroke or often sudden cardiac death . Despite their many benefits, antiplatelet agents, including low‐dose aspirin, are limited by their tendency to foster unwanted bleeding events . Thus, there is a compelling need to optimize CVD event reduction without accompanying untoward bleeding complications.…”
Section: Discussionmentioning
confidence: 99%
“…reviewed in ), and it is the acute thrombotic event that precipitates a myocardial infarction, stroke or often sudden cardiac death . Despite their many benefits, antiplatelet agents, including low‐dose aspirin, are limited by their tendency to foster unwanted bleeding events . Thus, there is a compelling need to optimize CVD event reduction without accompanying untoward bleeding complications.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a recently published meta-analysis which analyzed 12-month versus prolonged DAPT duration. [11] The authors reported that continuation of DAPT beyond 1 year was not associated with lower risk of ST, lower rates of major adverse CV, and cerebrovascular events, but did confer a higher bleeding risk. Our meta-regression analysis reflects the aforementioned findings, with a significant association between bleeding and non-CV mortality with 12-month DAPT, results also consistent with the findings of the DAPT trial [28] where bleeding events were related to trauma and cancer causes, in addition to the significant association between ST and MI, as well as mortality with short-term DAPT.…”
Section: Discussionmentioning
confidence: 99%
“…[8] Other previously published meta-analyses included fewer RCTs. [911] An updated meta-analysis evaluating the risks and benefits of DAPT for ≤6 months compared with the exact time point of 12 months is lacking. Our aim was to undertake a systematic review and meta-analysis of RCTs evaluating efficacy and safety of ≤6-month compared with 12-month DAPT after PCI with DES implantation.…”
Section: Introductionmentioning
confidence: 99%
“…The PEGASUS study concluded that ticagrelor significantly reduced the risk of MACE as compared with placebo. Recently, two meta-analyses [36, 37] showed that DAPT beyond 1 year among stabilised high-risk patients with prior MI decreased ischaemic events at the cost of an increase in major bleeding. Udell et al.…”
Section: Antiplatelet Therapymentioning
confidence: 99%